The Recovery of Mycobacterium avium Complex and Mycobacterium tuberculosis from Blood Specimens of AIDS Patients Using the Nonradiometric BACTEC NR 660 Medium. Issue 1 (28th January 2016) - Motyl, Mary R.; Saltzman, Brian; Levi, Michael H.; Mckitrick, John C.; Friedland, Gerald H.; Klein, Robert S.
Abstract : The ability of the nonradiometric BACTEC NR 660 aerobic 6A blood culture medium to support mycobacterial growth was investigated. During a 19-month period blood cultures from 140 AIDS patients were sent to the microbiology laboratory. After the cultures were incubated for seven days, aliquots of medium from the vials were centrifuged, sediments examined microscopically for mycobacteria, and cultured to mycobacterial media. Seventy-one AIDS patients (51%) had at least one blood culture positive for mycobacteria. There was a significant difference in the percent of female AIDS patients positive for mycobacteria compared to male patients (72% vs. 44%, P < 0.01). Forty-four percent of all subsequently positive cultures were detected by an acid fast stain of the specimen sediment. Subcultures from the BACTEC 6A suspensions were positive on mycobacterial media at one-seven weeks (mean three weeks) after planting. Sixtynine of the isolates were Mycobacterium avium complex, while two were Mycobacterium tuberculosis. Some bacteremias with M. tuberculosis may have been undetected because growth experiments with a reference strain showed that, in contrast to M. avium complex, M. tuberculosis did not increase in concentration in 6A medium.